Cell Death and Disease - Xu, Ke (Biochemistry, 2023)
Cell death is critical for embryo development and body growth. Several types of cell death have been discovered. The dysfunction of cell death is responsible for various diseases; however, the mechanism underlying cell death is not fully elucidated. Recent advances in cell death research have led to improved diagnosis, treatment, and clinical management of diverse diseases; however, novel therapeutic strategies are urgently needed. This book presents the most recent advances in cell death and related diseases.